2021
DOI: 10.24106/kefdergi.715624
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Poetry Focused Supportive Educational Program to Preschool Children's Phonological Awareness

Abstract: The study aims to examine the effect of the Poetry Focused Supportive Educational Program (PFSEP), which was prepared for preschool children, on children's phonological awareness skills. In order to support the phonological awareness of preschool children, poetry focused educational program was developed using phoneme awareness, rhythmic utterance and sound games. PFSEP's activity plans cover the phases of word awareness, syllable awareness, rhyme awareness and phoneme awareness, including phonological awarene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…In their study, Çetin (2019) found that the early literacy program they implemented had a lasting effect on phonological awareness skills. Similarly, Dinler and Cevher Kalburan (2021) concluded that the poetry-supported education program had a lasting effect on word, rhyme, initial/final sound, and syllable awareness skills. Van der Kooy-Hofland et al (2012) determined that a computer game focused on names and sounds had a lasting effect on children's phonological awareness skills.…”
Section: Examination Of the Persistence Of The Experimental Groupsmentioning
confidence: 99%
“…In their study, Çetin (2019) found that the early literacy program they implemented had a lasting effect on phonological awareness skills. Similarly, Dinler and Cevher Kalburan (2021) concluded that the poetry-supported education program had a lasting effect on word, rhyme, initial/final sound, and syllable awareness skills. Van der Kooy-Hofland et al (2012) determined that a computer game focused on names and sounds had a lasting effect on children's phonological awareness skills.…”
Section: Examination Of the Persistence Of The Experimental Groupsmentioning
confidence: 99%
“…Yapılan araştırmalar sesbilgisel farkındalığın ilkokuldaki okuma hızı ve okuma akıcılığını (Catts, Gillispie, Leonard, Kail ve Miller, 2002;Ehri, Nunes, Stahl ve Willows, 2001;Oudeans, 2003;Rakhlin, Cardoso-Martins ve Grigorenko, 2014) ve okuduğunu anlama becerilerini (Güldenoğlu, Kargın ve Ergül, 2016;Kjeldsen, Kärnä, Niemi, Olofsson ve Witting, 2014) yordadığını göstermektedir. Her ne kadar göç geçmişi, çocuğun yaşı, çocuğun zekası, dil güçlükleri, televizyon izleme (Frohlich, Petermann ve Metz, 2013), ev okuryazarlık ortamı (Foy ve Mann, 2003) ve kelime bilgisi (Frijters, Barron ve Brunello, 2000;Ouellette ve Haley, 2013) sesbilgisel farkındalık üzerinde önemli bir etkiye sahip olsa da, erken yıllarda sesbilgisel farkındalık becerilerinin çocuklara kazandırılabileceği araştırmalar tarafından ortaya koyulmaktadır (Akdal ve Kargın, 2019;Bayraktar ve Temel, 2014;Dinler ve Kalburan, 2021;Göle ve Temel, 2023;Kartal, Babür ve Erçetin, 2016;Lefebvre, Trudeau ve Sutton, 2011;Lovett, Lacerenza ve Borden, 2000;Lundberg, Larsman ve Strid, 2012;Parpucu ve Dinç, 2017;Suortti ve Lipponen, 2014;Tyler, Osterhouse, Wickham, Mcnutt ve Shao, 2014;Ukrainetz, Nuspl, Wilkerson ve Beddes, 2011).…”
Section: Introductionunclassified